Das Arkansas Echo : a year in the life of Germans in the nineteenth-century South - Condray, Kathleen M. (University of Arkansas Press, 2020)
"In examining Das Arkansas Echo, one of three German-language weeklies published in Arkansas at the end of the nineteenth century, this volume explores how German immigrants navigated life in the American South at the turn of the century"--